2010
DOI: 10.1177/104063871002200603
|View full text |Cite
|
Sign up to set email alerts
|

Development, Validation, and Utilization of a Competitive Enzyme-Linked Immunosorbent Assay for the Detection of Antibodies against Brucella Species in Marine Mammals

Abstract: Abstract. A competitive enzyme-linked immunosorbent assay (cELISA) was developed by using a wholecell antigen from a marine Brucella sp. isolated from a harbor seal (Phoca vitulina). The assay was designed to screen sera from multiple marine mammal species for the presence of antibodies against marine-origin Brucella. Based on comparisons with culture-confirmed cases, specificity and sensitivity for cetacean samples tested were 73% and 100%, respectively. For pinniped samples, specificity and sensitivity value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…The increased prevalence could also be due to crossreactivity with antibodies to other Gramnegative bacteria. Although not a part of this study, evaluation of cross-reactivity of the marine Brucella-based cELISA with other Gram-negative bacteria (Meegan et al, 2010) found that it did not occur with Yersinia enterocolitica O:9 antibody-positive sera; however, cross-reactivity was found with B. abortus-and B. melitensis-positive sera. Thus, because the ma-rine Brucella cELISA does cross-react with other terrestrial Brucella spp., it is unclear whether exposure to a marine or terrestrial strain was detected.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The increased prevalence could also be due to crossreactivity with antibodies to other Gramnegative bacteria. Although not a part of this study, evaluation of cross-reactivity of the marine Brucella-based cELISA with other Gram-negative bacteria (Meegan et al, 2010) found that it did not occur with Yersinia enterocolitica O:9 antibody-positive sera; however, cross-reactivity was found with B. abortus-and B. melitensis-positive sera. Thus, because the ma-rine Brucella cELISA does cross-react with other terrestrial Brucella spp., it is unclear whether exposure to a marine or terrestrial strain was detected.…”
Section: Discussionmentioning
confidence: 98%
“…Samples with .30% inhibition were considered positive. This test has not been validated in sea otters; however, based on comparisons with culture-confirmed cases, specificity and sensitivity for cetacean samples were 73% and 100%, respectively, and for pinnipeds 77% and 67%, respectively (Meegan et al, 2010). Additionally comparison testing revealed the marine-origin cELISA was more sensitive for detecting anti-Brucella antibodies in marine mammal samples than was the B. abortus tests available.…”
Section: Serologic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…19,26,30 Clinical manifestations of brucellosis in marine mammals are so far described only in cetaceans, with abortion and placentitis, orchitis, visceral and blubber abscesses, musculoskeletal lesions, and meningoencephalitis reported. 12,20,27 High levels of seropositivity are frequently reported in pinnipeds, and microbiologic isolation is reported in many pinniped species.…”
Section: Introductionmentioning
confidence: 99%
“…Our cELISA is based on the measurement of competition between the test sample and MAb for LPS, the major antigen of F. tularensis (14,24,25). Similar assays using MAb against LPS have been described for Brucella species (26,27). The typical ladder-like bands observed on WB demonstrated that both MAb and F. tularensis-infected human and mice serum contained antibodies predominantly recognizing the LPS antigen (Fig.…”
Section: Discussionmentioning
confidence: 99%